Measuring Interesting Amino Acid Patterns for Alzheimer's Disease Related Studies Targets on the Binding Site Using Association Rule Mining - D. Ponmary Pushpa Latha and D. Joseph Pushpa Raj (Journal of Applied Pharmaceutical Science, 2013)
Data mining techniques are used in various areas like stock exchange, education, bioinformatics, health care etc. The main purpose of data mining techniques is used to extract the useful and interesting information. Association Rule Mining (ARM) associates the different attributes and gives the most suitable rules from large database. Protein ligand binding is an important step in enzymatic mechanisms and in drug discovery. This research work gives the association rules for amino acid residues which are present in the binding site of Alzheimer’s Disease Related Studies targets. The data are collected from Protein Data Bank. Association rule mining is applied in the Alzheimer’s Disease Related Studies protein and the interesting rules for the amino acid residues present in the Alzheimer’s Disease Related Studies are formed. Ile and Ser are the amino acid residues which are having major role in the precedence of association rules of Alzheimer’s Disease Related Studies. This research work may support in identify new binding protein-ligand pairs and predict protein ligand binding in particular diseases.
Keywords: Association Rule Mining, Alzheimer' s Disease